2017
DOI: 10.1093/gbe/evx051
|View full text |Cite
|
Sign up to set email alerts
|

Burrowers from the Past: Mitochondrial Signatures of Ordovician Bivalve Infaunalization

Abstract: Bivalves and gastropods are the two largest classes of extant molluscs. Despite sharing a huge number of features, they do not share a key ecological one: gastropods are essentially epibenthic, although most bivalves are infaunal. However, this is not the ancestral bivalve condition; Cambrian forms were surface crawlers and only during the Ordovician a fundamental infaunalization process took place, leading to bivalves as we currently know them. This major ecological shift is linked to the exposure to a differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 102 publications
0
12
0
Order By: Relevance
“…As reported by earlier studies, mitochondrial PCGs may experience positive selection in deep-sea animals and thus may help them adjust their metabolism to tolerate the deep-sea conditions [ 37 , 38 , 39 ]. In the present study, potential positive selection was evaluated in deep-sea mussels by using CodeML in the PAML package.…”
Section: Discussionmentioning
confidence: 94%
“…As reported by earlier studies, mitochondrial PCGs may experience positive selection in deep-sea animals and thus may help them adjust their metabolism to tolerate the deep-sea conditions [ 37 , 38 , 39 ]. In the present study, potential positive selection was evaluated in deep-sea mussels by using CodeML in the PAML package.…”
Section: Discussionmentioning
confidence: 94%
“…Purifying selection is the predominant force in the evolution of mitogenomes, but because mitochondria are the main sites of aerobic respiration and are essential for energy metabolism, weak and/or episodic positive selection may occur against this background of strong purifying selection under reduced oxygen availability or greater energy requirements [8889]. As proven by many studies, mitochondrial PCGs underwent positive selection in animals that survived in hypoxic environments or had higher energy demands for locomotion, such as Tibetan humans, Ordovician bivalves, diving cetaceans and flying insects [19, 9092].…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondria are the energy metabolism centers of eukaryotic cells, which can generate more than 95% of cellular energy through oxidative phosphorylation (OXPHOS) [3]. Therefore, mitochondrial PCGs may undergo evolutionary selection in response to metabolic requirements in extremely harsh environments [1618]. Numerous studies have found clear and compelling evidence of adaptive evolution in the mitogenome of organisms from extreme habitats, including Tibetan humans [19], Chinese snub-nosed monkeys [20], Tibetan horses [2122], Tibetan wild yaks [23], galliform birds [24], and Tibetan loaches [25].…”
Section: Introductionmentioning
confidence: 99%
“…Six genes show significantly higher dN/dS ratios along branches leading to a DUI‐driven split (Figure ; Table ), in two cases with particularly large median values (~0.4 for cox3 , ~0.6 for nad4L and nad6 , but >1 for atp6 ). It is known that atp6 experienced several periods of noteworthy selective constraints (Plazzi et al., ) and that nad4L and nad6 have highly variable sequence (Plazzi et al., ). However, two facts lead us to discard the possible interpretation of these results as incidental features of these genes: (a) The same significant result obtained for cox1 , cox2 , and cox3 , which have a long, generally highly conserved sequence (Figure ); (b) the finding that, if not dN/dS ratio, at least either dN or dS rate is significantly higher along DUI‐splitting branches for all genes and the concatenated dataset, with the exception of atp8 (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, this tree was the result of the exploration of several maximum likelihood parameter combinations and is therefore the best single‐tree estimate of the whole‐mitochondrial phylogeny of bivalves. To explore the possibility of different selective pressures on different branches, we used the free‐ratios model, allowing an independent dN/dS ratio for each branch: It was already demonstrated that the free‐ratios model always outperforms the single‐ratio model (Plazzi, Puccio, & Passamonti, ). Equilibrium codon frequencies were used as free parameters.…”
Section: Methodsmentioning
confidence: 99%